The relationship between sleep problems and working memory in children born very preterm. Issue 1 (2nd January 2018) - McCann, Marie; Bayliss, Donna M.; Anderson, Mike; Campbell, Catherine; French, Noel; McMichael, Judy; Reid, Corinne; Bucks, Romola S.
ABSTRACT: In two studies, the relationship between sleep and working memory performance was investigated in children born very preterm (i.e., gestation less than 32 weeks) and the possible mechanisms underlying this relationship. In Study 1, parent-reported measures of snoring, night-time sleep quality, and daytime sleepiness were collected on 89 children born very preterm aged 6 to 7 years. The children completed a verbal working memory task, as well as measures of processing speed and verbal storage capacity. Night-time sleep quality was found to be associated with verbal working memory performance over and above the variance associated with individual differences in processing speed and storage capacity, suggesting that poor sleep may have an impact on the executive component of working memory. Snoring and daytime sleepiness were not found to be associated with working memory performance. Study 2 introduced a direct measure of executive functioning and examined whether sleep problems would differentially impact the executive functioning of children born very preterm relative to children born to term. Parent-reported sleep problems were collected on 43 children born very preterm and 48 children born to term (aged 6 to 9 years). Problematic sleep was found to adversely impact executive functioning in the very preterm group, while no effect of sleep was found in the control group. These findings implicate executive dysfunction as a possible mechanism by which problematic sleep adversely impacts upon cognition in children born very preterm, and suggest that sleep problems can increase the cognitive vulnerability already experienced by many of these children.